Model relating superconductive penetration depth and metallurgical phase separation in amorphous La70Cu30 - Arce, R.; de la Cruz, F.; Fink, H.J. (Elsevier, 1982)
Fil: Arce, R. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina